2004
DOI: 10.1007/s10021-004-0220-x
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Soil Processes to Climate Change: Results from Manipulation Studies of Shrublands Across an Environmental Gradient

Abstract: Predicted changes in climate may affect key soil processes such as respiration and net nitrogen (N) mineralization and thus key ecosystem functions such as carbon (C) storage and nutrient availability. To identify the sensitivity of shrubland soils to predicted climate changes, we have carried out experimental manipulations involving ecosystem warming and prolonged summer drought in ericaceous shrublands across a European climate gradient. We used retractable covers to create artificial nighttime warming and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
176
5
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(203 citation statements)
references
References 32 publications
12
176
5
3
Order By: Relevance
“…The percentage remaining of litter initial mass after 206 days ranged from 94.9% at 5°C and 50% moisture to 71.5% at 20°C and 200% moisture. Emmett et al (2004) reported data from litterbag experiments with C. vulgaris litter in a dry heathland in Denmark, in a wet heathland in Wales, and in the Oldebroekse heide in The Netherlands where we sampled the litter for this experiment. They found a remaining amount of initial mass after 200 days of 73, 82, and 80%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage remaining of litter initial mass after 206 days ranged from 94.9% at 5°C and 50% moisture to 71.5% at 20°C and 200% moisture. Emmett et al (2004) reported data from litterbag experiments with C. vulgaris litter in a dry heathland in Denmark, in a wet heathland in Wales, and in the Oldebroekse heide in The Netherlands where we sampled the litter for this experiment. They found a remaining amount of initial mass after 200 days of 73, 82, and 80%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Emmett et al (2004) manipulated temperature and moisture with a nonintrusive field experiment. They induced 2 months summer droughts and increased temperature with 0.5-2.0°C on other experimental plots.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Patil et al (2012), using the FASSET model to evaluate the sensitivity of winter wheat yield and soil N losses to stepwise changes in mean and variance of climatic variables in Denmark, showed an increase in mineral N leaching from winter wheat with increasing temperature, in particular for sandy loam soil at temperature increases above 2 • C. They also found higher simulated soil mineral N concentrations after crop harvest in summer and, therefore, higher risk of NO 3 N leaching during autumn and winter, which was ascribed to less N uptake by the crop and increased mineral N in soil profiles. The increased soil mineral N could be mostly attributed to climatic factors, in particular temperature that enhances mineralization processes through effects on soil microbial activity (Leirós et al, 1999;Emmett et al, 2004;Patil et al, 2010). In a synthesis of results from 32 studies on attempting to predict the influence of climate changes on terrestrial ecosystems, temperature increase of 2.4 • C was found to increase soil respiration by 20%, whereas net N mineralization rates increased by 46% (Rustad et al, 2001).…”
Section: Climate Effectsmentioning
confidence: 99%
“…Soil moisture appears to be the primary variable affecting soil enzyme activity (Sardans et al, 2008). N mineralisation and nitrification are related to temperature and indirectly to rainfall (Emmett et al, 2004). The overall effects depend on how changes affect soil moisture during the summer season (Leirós et al, 1999), on the countering effects of growth enhancement from increased carbon inputs and increased nitrate uptake by vegetation (Ineson et al, 1998a;Ineson et al, 1998b).…”
Section: Position Ofmentioning
confidence: 99%